Accu-Vital Monitor - Aya Ghazal; Mennat Allah Khayat (My University, 2023)
A multi-parameter patient monitoring system is a compact and portable device designed to facilitate easy movement and use in various healthcare settings. This system incorporates sensors to measure essential vital signs, including blood pressure, heart rate, temperature, electrocardiogram (ECG), and blood glucose levels. Its small size and lightweight design make it highly maneuverable, allowing healthcare professionals to conveniently transport and position the device as needed. The system's portability enables flexible monitoring capabilities, enabling healthcare providers to assess patients' health status in different areas of a hospital or even during patient transfers. With its user-friendly interface and comprehensive data collection, analysis, and display functionalities, the multi-parameter patient monitoring system empowers healthcare professionals to make informed decisions and provide timely interventions. The combination of its compact size, ease of movement, and advanced monitoring capabilities makes it an indispensable tool for efficient and effective patient care.